Evaluation of the surface and catalytic properties of the ethylene and oxygen adsorption process on gold catalysts supported on mixed oxides CeZr (2017)
Abstract. Surface and catalytic properties of mixed oxides CeO2, Au/CeO2, CeZr and Au/CeZr, during the total oxidation of ethylene is presented in this work. Four types of supports were used: synthesised and commercial CeO2 and CeZr mixed oxides. Synthesised supports were prepared by pseudo sol gel method while commercial supports were provided by Solvay-Rhodia. The mass CeO2/ZrO2 ratio was 0.8/0.2 for the synthesised support and 0.6/0.4 for the commercial one. Gold was subsequently deposited via direct anion exchange. XRD and Raman spectroscopy showed the effective formation of the fluorite type structure on each catalyst. Textural properties were determined via N2 adsorption, demonstrating the low influence of gold deposited as active phase. Temperature programmed desorption (TPD) and IR operando spectroscopy were used to stablish the fluid-surface interaction, elucidate the reaction mechanism during the oxidation reaction and determine the role of gold as active phase. Results show that there is no adsorption of ethylene or oxygen on any of the catalysts at room temperature, despite increasing the amount of gold deposited from 1 to 2%. In fact, only catalysts with gold are active for the oxidation reaction and only at temperatures above 100 °C. The formation of formate and carbonate species as intermediary precursors for the subsequent CO2 desorption, are seen as responsible for the oxidation of ethylene following the Mars and Van Krevelen model.